N-heterocyclic linkers from 1, 2-diaza-1, 3-dienes for dye-sensitized solar cells: DFT calculations, synthesis and photovoltaic performance. (October 2017) - Fattori, Alberto; Majer, Roberta; Mazzanti, Andrea; Ottaviani, Maria Francesca; Modelli, Alberto; Mantellini, Fabio; Santeusanio, Stefania
Abstract: Organic dyes for dye-sensitized solar cells (DSSC) are generally constituted by chemical groups that act differently as electron donor (D) and acceptor (A) bridged by a linker. Three new push-pull D–π–A structured dyes (SIP1, SIP3, SIP4 ) having imidazo[1, 2- a ]pyridine heterocycles as additional π-conjugated linker were designed and synthesized. Triphenylamine (TPA) was introduced as electron-donor unit and cyanoacetic acid or double rhodanine acetic acid were employed as anchoring groups in different positions of the heterocyclic core. DSSC devices with these dyes were assembled and tested using different electrolytes and dye baths. Finally, the related photovoltaic performance was measured. The Voc values were found to influence the overall behaviour of the cells related to the electrolyte composition. DFT calculations showed a theoretical trend for the electron transfer ability of the different dyes, and correlation with the real photovoltaic performance was discussed.